Shear wave splitting of the 2009 L'Aquila seismic sequence: fluid saturated microcracks and crustal fractures in the Abruzzi region (Central Apennines, Italy). Issue 3 (28th January 2016) - Baccheschi, P.; Pastori, M.; Margheriti, L.; Piccinini, D.
Abstract: The Abruzzi region is located in the Central Apennines Neogene fold-and-thrust belt and has one of the highest seismogenic potential in Italy, with high and diffuse crustal seismicity related to NE–SW oriented extension. In this study, we investigate the detailed spatial variation in shear wave splitting providing high-resolution anisotropic structure beneath the L'Aquila region. To accomplish this, we performed a systematic analysis of crustal anisotropic parameters: fast polarization direction ( φ ) and delay time ( δt ). We benefit from the dense coverage of seismic stations operating in the area and from a catalogue of several accurate earthquake locations of the 2009 L'Aquila seismic sequence, related to the M w 6.1 2009 L'Aquila main shock, to describe in detail the geometry of the anisotropic volume around the active faults that ruptured. The spatial variations both in φ and δt suggest a complex anisotropic structure beneath the region caused by a combination of both structural- and stress-induced mechanisms. The average φ is NNW–SSE oriented (N141°), showing clear similarity both with the local fault strike and the SHmax . In the central part of the study area fast axes are oriented NW–SE, while moving towards the northeastern and northwestern sectors the fast directions clearly diverge from the general trend of NW–SE and rotate accordingly to the local fault strikes. The above-mentioned fault-parallel φ distribution suggests that the observed anisotropy is mostly controlled by the local fault-related structure. Toward the southeast fast directions become orthogonal both to strike of the local mapped faults and to the SHmax . Here, φ are predominantly oriented NE–SW; we interpret this orientation as due to the presence of a highly fractured and overpressurized rock volume which should be responsible of the 90° flips in φ and the increase in δt . Another possible mechanism for NE–SW orientation of φ in the southeastern sector could be ascribed to the presence of a buried, deep NE–SW oriented fault system. δt, both unnormalized and normalized, does not show any clear evidence of increasing with increasing depth indicating that the anisotropy is confined primarily to the shallower crustal layers (∼10 km depth). Interpolating δt show that higher values are found at the edges of the main patches of the rupture related to the 2009 main shock, while lower values are limited in the central part of the fault plane, where the coseismic slip was higher. We infer that in the areas surrounding the ruptured region, lateral variations in material properties caused overpressurized fluid conditions, while within the main shock ruptured area, high energy released produced an open crack system such that overpressurization was not possible.